Early postpartum hormonal therapy improves fertility of dairy cows - Jeffrey S. Stevenson; M. BenMrad (Kansas Agricultural Experiment Station Research Reports, 1985)
A study of 234 Holstein cows was conducted to determine if hormonal treatments of gonadotropin-releasing hormone (GnRH or Cystorelin®) and(or) prostaglandin F2α (PGF or Lutalyse®) given early after calving would improve subsequent fertility of dairy cows. Treatment of cows having abnormal conditions associated with calving (puerperal problems) reduced interval from calving to conception by 43 to 48 days when GnRH was given once between days 10 and 14 postpartum or when PGF was administered once between 20 and 24 days after calving compared with cows given only saline (controls). The reduction in days open was 27 to 29 days overall for all cows (normal and abnormal) treated with either hormone compared with controls. Cows (normal and abnormal) given either hormone required 26 to 41 % fewer inseminations per conception than controls. Reasons for improved fertility are discussed. We conclude that early postpartum treatments with GnRH or PGF improved fertility of dairy cows, especially those that experienced puerperal problems.; Dairy Day, 1985, Kansas State University, Manhattan, KS, 1985;
Keywords: Kansas Agricultural Experiment Station contribution; no. 86-94-S; Report of progress (Kansas Agricultural Experiment Station); 484; Dairy; Fertility; Gonadotropin-releasing hormone (GnRH); Prostaglandin F2-α; Conception